DIVERSI DAN PELAKU KECELAKAAN LALU LINTAS - Prasetya, Rendra Kurniawan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2016)
Traffic and road transport are important in improving the social mobility of the community. Traffic problems are a national-scale problem and relate to community development. The most important factor in traffic is the matter of traffic accidents causing death. Perpetrators in traffic accidents may be subject to legal or off-court settlement efforts. The regulation on traffic and road transport nationally is regulated in Law Number 22 Year 2009 on Traffic and Road Transport. The law is a guideline in the prosecution of traffic violations. This provision is expected to adhere to and comply with the entire legal rules of driving or traffic, so that it creates safety, security and smooth traffic and improve the welfare of the community. The research method used is normative law research method. The approach is done constitution approach, concept approach, philosophy approach and case approach. Law materials source is primary, secondary and tertiary law materials with the analysis using deductive silogism. Law enforcement is the process of undertaking efforts to uphold or functioning legal norms in real terms as a behavioral guide in traffic or legal relationships in the life of society and state. Law enforcement is an attempt made to make the law both formal and material in nature, as a code of conduct in every legal act, both by legal subjects concerned and law enforcement officials authorized by law to ensure the proper functioning of the legal norms applied in the society life and state.